OS4.1 A risk calculator to predict the need for an intervention within a patient's estimated lifetime for incidentally-found asymptomatic meningiomas. (19th September 2018) - Islim, A I; Mohan, M; Moon, R; Kolamunnage-Dona, R; Rathi, N; Mills, S J; Brodbelt, A R; Jenkinson, M D
Abstract: Background: 30% of newly-diagnosed meningiomas are incidental findings. There is no consensus on the optimal management. The aim of this study was to develop a risk calculator to enable identification of patients at risk of active monitoring failure who will require an intervention within their estimated lifetime. Material and Methods: Active monitoring failure was defined as: new symptoms, MRI progression (absolute growth rate ≥ 2 cm3/year or absolute growth rate ≥ 1 cm3/year + relative growth rate ≥ 30%/year) or loss of treatment options. A prognostic model was developed using MRI and patient co-morbidity (age-adjusted Charlson index) in a retrospective cohort (2007–2015). Results: 385 patients were included (403 meningiomas). Mean age at diagnosis was 62.6 years (SD= 12.0); 301 (78.2%) were female. Over a median of 36.0 months (range: 3–120), 1688 MRI were performed (mean=4 scans/patient). 44 (10.9%) meningiomas were classed as failed active monitoring; reasons being radiological progression (n=29), new symptom development (n=12), development or worsening of peritumoural oedema (n=12), meningioma volume exceeding 10 cm 3 (n=9) and venous sinus invasion (n=7). Nineteen (43.2%) patients had > 1 reason for failing active monitoring. Median time to failure was 33.0 months (range: 5–102). Model parameters were based on statistical and clinical considerations. These included: increasing tumour volume (HR=2.17 [95% CI=1.53–3.09], p<0.001), peritumoural signal change (HR=1.58 [95% CI=0.65–3.85], p=0.313), FLAIR/T2 hyperintense meningiomas (HR=10.6 [95% CI=5.39–21.0], p<0.001) and proximity to critical neurovascular structures (HR=1.38 [95% CI=0.74–2.56], p=0.314). Discriminatory power of the model was excellent (Harrell's C statistic=0.89). Patients were stratified based on the model into low, medium and high-risk groups. Low-risk patients had non-oedematous, small iso/hypointense meningiomas, distant from neurovascular structures. Rates of active monitoring failure at 5-years were 3%, 28% and 75% respectively. After 5-years of follow-up the probability of failed active monitoring plateaued in all risk groups. Older patients with co-morbidities (age-adjusted Charlson index ≥ 6) were 15-times more likely to die than to receive intervention at 5-years following diagnosis, regardless of risk-group. Conclusion: Most meningiomas remain clinically and radiologically stable. Patients with Charlson index ≥ 6 do not require active monitoring. Low-risk patients require less frequent MRI monitoring. Follow-up beyond 5-years may not be required for all patients. Stratifying follow-up according to risk-group has the potential to reduce the cost of healthcare.